Pullus, gallus et gallina : déclinaisons antiques - Nicole Blanc (Revue d'ethnoécologie)
This paper aims to give a brief overview of the main representations of the Gallinacea family in the Graeco-Roman world. The cock (gallus) by its beauty and its ardor in fighting dominates imagination and is most often pictured; it enjoys a reputation for pride and bravery that allows it to be a symbol of victory. The young chicken (pullus) is associated with the religious and political life under the Republic, as acting in the ritual of divination of the tripudium. Being a product of breeding and consumption, the hen (gallina) questions agronomic practices; fattening techniques turn it into an expensive and gastronomic food.